IN PAYING COMPENSATION FOR ACCIDENTS AND OCCUPATIONAL DISEASES IN AUTOMOTIVE ENTERPRISES - Abdurakhmanov Abdurashid (Web of Journals Publishing, 2024)
Foreign experience in the prevention of accidents and occupational diseases and compensation for injured persons in the automotive industry is of great importance. Studying best practices in this area helps to improve worker safety, ensure effective management of the economy and ensure social justice. This article studies the experiences of Germany, China, Japan and Russia. Based on the results of the analysis, the necessary conclusions and recommendations were developed.
Keywords: Occupational safety, environment, accidents, occupational diseases, injuries, safety training, training courses, compensation.